Pengembangan Aplikasi “DELIMA” sebagai Upaya Deteksi Dini Kehamilan Bermasalah - Kumalasari, Intan; Maksuk; Yuniati, Faiza; Rangga, Aidil Dwi; Fathurrahman, M. Dimas; Aulia, Estu (STIKES Ngesti Waluyo, 2023)
The maternal mortality rate (MMR) is one of the main indicators of a country's health status. This high mortality rate indicates low health status caused by limited access and quality of health services, as well as low knowledge of mothers and families in recognizing danger signs in pregnancy. This study aims to produce applications that can be used to detect the risk of problematic pregnancies. The research method used was a research and development design (R and D) with the ADDIE design model, where the resulting product is obtained by analyzing potential problems based on literature studies and information gathering; proceed with product design; developing products through validity testing by media experts and material experts; product implementation as well as the final evaluation of the feasibility and usefulness of the product. The results of the media expert validation obtained a score of 75% which means the application is feasible to use; the material expert's assessment score is 100% which means the product is very feasible to develop; the implementation stage obtains a score of 77.3% which means the application is feasible to use. In the evaluation stage, 80% of respondents gave a positive response to the feasibility of the application, and in the aspect of understanding, the application is considered to be able to increase the understanding of pregnant women by 83%. The DELIMA application has been disseminated in two public health centers in Palembang, and expressed support for implementing this application as an effort to capture at-risk pregnant women in their work areas. Given its usefulness in early detection of at-risk pregnancies, it is hoped that the City Health Office can recommend this application to be used by all Public health centers in Palembang City.